Effect of polyamines on leaf rolling during drought stress in Ctenanthe setosa (Rosc.) Eichler - Kadıoğlu, Asim; Turgut, Rabiye; Ünsal, Zeynep Narçin; Saruhan, Neslihan (My University, 2002)
The effects of the three main polyamines, putrescine, spermine, and spermidine, on the degree of leaf rolling in Ctenanthe setosa were investigated. In addition, the interactions between the amounts of endogenic polyamines and leaf rolling were determined during drought stress. The polyamines were sprayed onto the leaves at 5 10-5 M. The degree of leaf rolling decreased in plants that were treated with the polyamines as compared to the controls. Also, we observed an increase in the amounts of putrescine, spermine, and spermidine of untreated leaves with increasing stress or degree of leaf rolling, but they decreased at the highest degrees of leaf rolling. Polyamines are linked specifically to mechanisms of adaptation to water deficit-stress in Ctenanthe setosa.